Some Extension Results in Classical Integral Inequalities - Belaidi, Benharrat; El Farissi, Abdallah; Dahmani, Zoubir (Int. J. Open Problems Comput. Math, 2012)
In this paper, we give new extensions of the classical Hermite-Hadamard and Fejer integral inequalities. Some applications of these extensions are also presented.
Keywords: Convex functions; Fejer inequality; Hermite-Hadamard inequality.